Current-Voltage Response of Cold White LED Strip to Radiotherapeutic Electron and Photon Beams: A Preliminary Study. (March 2020) - Damulira, E; Yusoff, MNS; Omar, AF; Taib, NHM; Kamal, SAM; Dani, SM; Abdullah, R
Abstract: Photonic devices such as photodiodes, phototransistors, solar cells, and charge-coupled devices (CCDs) have been associated with clinical radiation detection in recent studies. Light Emitting Diodes (LEDs) are of low-cost in comparison to photodiodes and available in various flexible designs, including surface mount devices (SMDs). LEDs are purposely designed to emit light, but they can also be implemented for detecting light in a photovoltaic mode. Despite the LED-related merits, a few studies, compared to other photonic devices, especially photodiodes, have adopted them as medical radiation detectors. This research hence exploits the LED's dual applicability by investigating a cold/cool white LED strip current-voltage (C-V) signal response to photon and electron beams. Radiation parameters such as beam energy, angle of incidence, field size, surface source distance (SSD), and monitor units (prescribed dose) were varied. According to the obtained results, the electron beams induced a 10% higher C-V signal compared to photon beams. An angular dependence was also observed, i.e., the C-V signal fluctuated due to a variation in the irradiation angles; -45°, -25°, 0°, 25°, 45°, and radiation type – photon and electron beams. The C-V signal response to SSD alterations additionally produced bimodal signal graphs, skewed towards shorter SSDs, for all the beams used in this study. Finally, the C-V signal was generally linear to the prescribed dose for both the photon and electron beams. Overall, the response of LEDs to photon and electron beams separately exhibited a similar signal trend for the beam energy, field size, angular dependence, and SSD parameter variations. On the other hand, dose linearity produced contrasting signal trends across the photon and electron beams.